ECHEVERRÍA, Javier (2023). Leibniz, el archifilósofo, Madrid: Plaza y Valdés. - Fernández García, Francisco J. (Daimon Revista Internacional de Filosofia, 2025)
Reseña de ECHEVERRÍA, Javier (2023). Leibniz, el archifilósofo, Madrid: Plaza y Valdés, 381 pp.